Global Public Health Surveillance under New International Health Regulations - Michael G. Baker; David P. Fidler (Emerging Infectious Diseases, 2006)
The new International Health Regulations adopted by the World Health Assembly in May 2005 (IHR 2005) represents a major development in the use of international law for public health purposes. One of the most important aspects of IHR 2005 is the establishment of a global surveillance system for public health emergencies of international concern. This article assesses the surveillance system in IHR 2005 by applying well-established frameworks for evaluating public health surveillance. The assessment shows that IHR 2005 constitutes a major advance in global surveillance from what has prevailed in the past. Effectively implementing the IHR 2005 surveillance objectives requires surmounting technical, resource, governance, legal, and political obstacles. Although IHR 2005 contains some provisions that directly address these obstacles, active support by the World Health Organization and its member states is required to strengthen national and global surveillance capabilities.